1999
DOI: 10.1002/(sici)1521-4028(199912)39:5/6<283::aid-jobm283>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal distribution of naturally occurringBacillus spp. and other bacteria on the phylloplane of soybean under field conditions

Abstract: Bacterial populations were surveyed on phylloplane of field‐grown soybean every 20 days in south‐ern Buenos Aires, Argentina. The crop was disease‐free and no pesticides were applied. Out of 523 bacterial isolates (mainly Gram positive bacteria) from upper and lower leaves, 134 of them were Bacillus spp. Bacillus pumilus was the dominant species followed by Bacillus subtilis. The proportion of Bacillus spp. decreased from 80% of all bacterial isolates in early stages to 0% at harvest, whereas the diversity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 7 publications
2
11
1
Order By: Relevance
“…In Argentina, a reduction in the diversity of Bacillus spp. from the soybean phyllosphere occurred throughout the season, with only one species (B. pumilus) being recovered late in the season (2). The role of heat and dessiccation stresses in the seasonal succession observed in phyllosphere bacterial communities remains an open question.…”
Section: Discussioncontrasting
confidence: 60%
“…In Argentina, a reduction in the diversity of Bacillus spp. from the soybean phyllosphere occurred throughout the season, with only one species (B. pumilus) being recovered late in the season (2). The role of heat and dessiccation stresses in the seasonal succession observed in phyllosphere bacterial communities remains an open question.…”
Section: Discussioncontrasting
confidence: 60%
“…Bacillus species are typical inhabitants of the rhizosphere, but they are also commonly present on the surface of plants. B. subtilis and B. megaterium had been detected in the olive phylloplane at all times during the year[20], and B. pumilis was found to be an efficient colonizer of the soybean phylloplane[21]. B. pumilis was isolated from the phyllosphere of an apple orchard in Northern Germany and was an efficient antagonist to Venturia inaequalis , the apple scab pathogen[22].…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies of Huang et al (2005) and Chiou and Wu (2001), several antagonistic bacteria were selected and examined for their biocontrol activities. Several studies reported biocontrol activity of B. pumilus strains against plant fungal pathogens (Arias et al 1999). In this study, chitinolytic B. pumilus SG2 was selected and its potential biocontrol activity was demonstrated by a dual culture assay.…”
Section: Discussionmentioning
confidence: 99%